DANANTARA AND EFFORTS TO SUPPORT INDONESIA AS A WORLD CENTER FOR SHARIA FINANCE: STRATEGIC ANALYSIS - Ali Akhmadi (RADJA PUBLIKA, 2026)
Indonesia has the ambition to become a global Islamic financial center, leveraging its significant potential. This study analyzes the strategy of Danantara, a state-owned financial holding company, in supporting this national ambition. Through a bibliometric analysis of relevant literature (100 articles, 980 citations, h-index 14) using VOSviewer and a review of the proposed strategic framework, this study identifies key thematic clusters: finance, halal industry, financial literacy, MSMEs, digital Islamic banking, and stakeholder engagement. The findings highlight Danantara's central role as a candidate for an Islamic Financial District (IFD). A comprehensive five-pillar strategy is considered crucial: 1) strengthening the ecosystem and institutions; 2) developing world-class physical and digital infrastructure centered in Danantara; 3) improving the quality of human resources and attracting global talent; 4) developing competitive product innovations; and 5) developing strong international markets and promotions. This study concludes that the effective implementation and orchestration of this integrated strategy by Danantara is crucial for Indonesia to realize its vision as a leading global Islamic financial center, contributing significantly to the national economy and its international position.